2022
DOI: 10.3389/fimmu.2022.818017
|View full text |Cite
|
Sign up to set email alerts
|

STAT6 Blockade Abrogates Aspergillus-Induced Eosinophilic Chronic Rhinosinusitis and Asthma, A Model of Unified Airway Disease

Abstract: Unified airway disease, including concurrent asthma and chronic rhinosinusitis (CRS), is a common, but poorly understood disorder with no curative treatment options. To establish a murine model of chronic unified eosinophilic airway inflammation, mice were challenged with Aspergillus niger, and sinonasal mucosa and lung tissue were evaluated by immunohistochemistry, flow cytometry, and gene expression. Inhalation of A niger conidia resulted in a Th2-biased lung and sinus inflammation that typifies allergic ast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Thus, it is possible that STAT6, but not STAT1 and STAT3, might be a crucial signal transducer in the development of ECRS. STAT6 is essential for ECRS, as demonstrated by Sun et al 39 In this article, the authors focused on the functions of STAT6 rather than other STAT family members in ECRS. Another study using JAK inhibitor-treated eosinophilic CRSwNP in a mouse model indicated that by inhibiting STAT6 phosphorylation, the Th2 response and eosinophilic inflammation can be reduced.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, it is possible that STAT6, but not STAT1 and STAT3, might be a crucial signal transducer in the development of ECRS. STAT6 is essential for ECRS, as demonstrated by Sun et al 39 In this article, the authors focused on the functions of STAT6 rather than other STAT family members in ECRS. Another study using JAK inhibitor-treated eosinophilic CRSwNP in a mouse model indicated that by inhibiting STAT6 phosphorylation, the Th2 response and eosinophilic inflammation can be reduced.…”
Section: Discussionmentioning
confidence: 98%
“…This pathway is involved in the polarization of T helper cells and colony-stimulating factors [163,164] and could potentially be a target for future therapeutic options in CRS. It has been documented that phosphorylated STAT6 but not STAT1 and STAT3 are significantly increased in the sinonasal mucosa after allergen stimulation in a murine model of chronic eosinophilic airway inflammation [165,166], and STAT6 gene silencing ameliorated allergic rhinitis [167] and inhibited allergic airways inflammation [168,169]. In an interventional study of mice, topical tofacitinib administration was shown to be an effective treatment for eosinophilic CRSwNP by inhibiting phosphorylation, especially of STAT6, and decreasing the levels of eosinophil cationic protein and eotaxins [170].…”
Section: Targeting Janus Kinasesmentioning
confidence: 99%
“…However, when inhibiting STAT6, IL-4 or IL-13 exhibited to reduce FABP4 expression, suggesting that the role of FABP4 is regulated by its binding to STAT6, implying the important role of STAT6 in asthma inflammation [139,140]. By interfering with the interaction of STAT-6-MAP kinase with ERK1/2 and p38, or suppressing STAT-6 serine phosphorylation, STAT-6 can be inhibited from activation and acetylation [141][142][143]. Serine kinases are essential in phosphorylating serine residues in STAT-6 to promote its transactivation, therefore, inhibitors of these kinases related to FA and amino acid metabolism may be potential targets in asthma treatment.…”
Section: Targets In Il-4/il-13/janus Kinase/stat-6 Pathwaymentioning
confidence: 99%